The perfect letter [compact disc, unabridged] : a novel - Harrison, Chris, 1971 July 26- (Brilliance Audio, 2015)
As the longtime host of ABC's hit shows The Bachelor and The Bachelorette, Chris Harrison has witnessed the joys and heartbreak of men and women searching for everlasting love. A true romantic at heart, he believes that everyone deserves their own fairytale ending. Now, in his first work of fiction, Chris draws on his unique insights and wisdom in a remarkable debut novel that explores love and its consequences.